BITTERLICH SAMPLING METHOD APPLIED IN MIXED OMBROPHILOUS FOREST - FIORENTIN, Luan Demarco; MIRANDA, Rodrigo Otávio Veiga de; JUVANHOL, Ronie Silva; PÉLLICO NETTO, Sylvio; NASCIMENTO, Rodrigo Geroni Mendes; MACHADO, Sebastião do Amaral (Brazilian Journal of Biometrics, 2016)
Bitterlich sampling has great potential for use in the native forest inventories. Therefore, this study aims to evaluate the behavior of this sampling method, testing the effect of different Basal Area Factors (BAFs) on the prediction of the diameter distribution, as well as the estimation of the population parameters of a Mixed Ombrophilous Forest. The data came from a census carried out in a forest fragment, located in Curitiba, PR. Forest inventories were simulated for nine BAFs, aimed to estimate the mean diameter, as well as the number of trees (N), basal area (G) and volume per hectare (V). The diametric distributions sampled were compared using Graybill’s F test. The BAFs affect the precision of the method. The BAFs have showed statistical discrepancy among themselves in the estimates of diameter distribution, N, G and V. The estimators of the N, G and V per hectare are more consistent when using the basal area factors equal or less than 1 to the sampled population. However as the basal area factor 1 met the condition with the minimum number of trees, it will be more appropriate to also meet the condition of minimum cost, which proves the hypothesis formulated in this work.